Evaluación del contenido de metales pesados en peces de agua dulce (bocachico, campeche y dama) en la zona de Influencia de la U.T.E.Q. - Alcívar Choez, Gabriela Mariana (2015)
This research aims to assess the content of heavy metals in freshwater fish (Bocachico, Campeche, and dama), in the area of influence of the State Technical University Quevedo. We analyzed the presence of heavy metals in the species listed above considering a sample of 200gr per treatment, since this research required of 9 treatments with 3 replications (study 27 samples), is required a total of 5400 gr of fish meat of the three species. Then of the digested sample by wet and dry, we analyzed the presence of lead, mercury and arsenic, for this, considering the complexity of the analyzes they went to the laboratories LABOLAB S. A. of the city of Quito, and proceeded to analyze using the following equipment: for lead (Pb) GF-AAS, methylmercury CV-AFS and arsenic FI-HG-AAS and internal methods as APHA 3500pb, APHA 3500 MHg, APHA 3500 Ace. The factors evaluated were to: zone of influence (Quevedo, San Carlos, Multipurpose "BABA"; and B: three species of fish (Bocachico, Campeche, Dama), to establish levels of difference between the treatments, i applied a Tukey test at the >0.05. The results were analyzed using the statistical package Statgraphics Centurion The results of the analysis of lead, mercury and arsenic in the analyzed samples showed that both in the factor TO( zone of influence) as in the B-factor (fish species) is below the limit established in accordance with the European Union on the content of heavy metals and other contaminants through fishing Regulation (EC) No 1881/2006 which was modified to turn in (EC) No. 629/2008, which recommended a limit of 1.0mgHg.Kg-1 for large fish with respect to mercury and lead 0.3 Hg.Kg-1. Since it is normally noted in the contents of these metals, it is recommended that any of these areas, either: Quevedo, San Carlos and Multipurpose Baba fish are reliable......